Technological aspects of obtaining the chewable tablets with oats extract and quercetin - I. R. Andriichuk; L. L. Davtyan (Zaporozhye State Medical University, 2014)
Aim. In the complex treatment of diseases that are associated with the stress or the overfatigue, much attention is paid to the drug therapy. On the Ukrainian pharmaceutical market synthetic drugs dominate among other drugs of tonic effect. The aim of our research is to develop chewable tablets with dry oats extract and quercetin. Methods and results. During our work qualitative and quantitative composition of chewable tablets as well as conditions of granulation and tableting processes have been substantiated, the technological process for preparing solid dosage form has been developed, technological flowchart has been composed. Conclusion. This makes possible to improve composition and technology, and to expand the spectrum of pharmacological effects of the known drug Kvertin (PAO SPC «Borshchahivskiy CPP»).